Terminology Bulletin No. 346 : currency units (UN New YorkUS, 1993)
Gives a list, in alphabetical order by name of country, of the official basic units of currency and the appropriate currency abbreviations that are officially in use as at 19 March 1993. The countries listed are States Members of the UN, members of specialized agencies or parties to the Statute of the International Court of Justice.
Keywords: TERMINOLOGY